Implementasi Evaluasi Pembelajaran Berbasis Student Led Conference (SLC) di Sekolah Dasar - Faizatul Khoeriyah; Rahmat Kamal (Program Studi PGSD Universitas Madako Tolitoli, 2023)
Student Led Conference (SLC) is a form of evaluation in learning activities that aims to get an overview of the achievement of the learning process that students have gone through at Al Azhar 60 Pekalongan Islamic Elementary School. Researchers used a qualitative method with a descriptive approach. The subjects of this study were class 1B students totaling 25 people and also involved 2 teachers. The data collection method used observation, interview and documentation techniques. The data analysis process uses Miles & Huberman's interactive data collection, namely data reduction, data display and drawing conclusions or conclusions. The results of this study show that during the implementation of SLC, teachers, students and parents have the opportunity to access information about how far students' academic learning targets have been achieved. SLC also makes it easier for students to choose which learning they are interested in, so that students can develop their abilities according to what they want. This research also makes parents aware of their children's personalities and gives them the opportunity to learn more about their children.